The Adaptogens Rhodiola and Schizandra Modify the Response to Immobilization Stress in Rabbits by Suppressing the Increase of Phosphorylated Stress-activated Protein Kinase, Nitric Oxide and Cortisol - Alexander Panossian; Marina Hambardzumyan; Areg Hovhanissyan; Georg Wikman (AboutScience Srl, 2007)
Adaptogens possess anti-fatigue and anti-stress activities that can increase mental and physical working performance against a background of fatigue or stress. The aim of the present study was to ascertain which mediators of stress response are significantly involved in the mechanisms of action of adaptogens, and to determine their relevance as biochemical markers for evaluating anti-stress effects in rabbits subjected to restraint stress. Blood levels of stress-activated protein kinase (SAPK/JNK), the phosphorylated kinase p-SAPK/p-JNK, nitric oxide (NO), cortisol, testosterone, prostaglandin E2, leukotriene B4 and thromboxane B2 were determined in groups of animals prior to daily oral administration of placebo, rhodioloside or extracts of Eleutherococcus senticosus, Schizandra chinensis, Rhodiola rosea, Bryonia alba and Panax ginseng over a 7 day period. Ten minutes after the fi nal treatment, animals were immobilized for 2 hours and blood levels of the markers re-determined. In the placebo group, only p-SAPK/p-JNK, NO and cortisol were increased significantly (by 200-300% cf basal levels) following restraint stress, whilst in animals that had received multiple doses of adaptogens/stress-protectors, the levels of NO and cortisol remained practically unchanged after acute stress. Rhodioloside and extracts of S. chinensis and R. rosea were the most active inhibitors of stress-induced p-SAPK/p-JNK. E. senticosus, B. alba and P. ginseng exerted little effect on p-SAPK/p-JNK levels. It is suggested that the inhibitory effects of R. rosea and S. chinensis on p-SAPK/p-JNK activation may be associated with their anti-depressant activity as well as their positive effects on mental performance under stress.